Hydrogels for 3D Printing (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Discover cutting-edge research in our Special Issue, titled "Hydrogels for 3D Printing". This collection of articles and reviews delves into the multifaceted world of hydrogel-based 3D printing, covering essential topics such as material formulation, printing techniques, and post-processing methods. From optimizing rheological properties to enhancing cell viability, each contribution offers valuable insights into the transformative potential of hydrogels across various applications, including tissue engineering and regenerative medicine. Do not miss this invaluable resource for researchers, engineers, and practitioners striving to advance the field of 3D printing.